Escherichia coli recombinant sperm immobilizing factor RecX as a potential vaginal contraceptive - Monika Answal; Vijay Prabha (BMC, 2018)
Abstract Background To control the overpopulation and unintended pregnancies, vaginal contraceptives have gained recent surge of interest because of its topical application with possible avoidance of systemic effects. However non-specific cytotoxicity associated with detergent-based synthetic vaginal contraceptive agents limits their use and generates considerable interest in the development of vaginal contraceptives of biological origin for controlling reproduction and ultimately growing population. In this study, we have cloned, over-expressed an Escherichia coli gene encoding a sperm immobilizing factor (SIF) that inhibits sperm motility for the development of vaginal contraceptive from a biological source i.e. E. coli. The contraceptive efficacy of the Escherichia coli recombinant sperm immobilizing factor (r-SIF) was also determined. Methods Genomic DNA library of an E. coli strain isolated from semen sample of an infertile male was constructed for the identification and cloning of E. coli SIF coding gene. This gene was sub-cloned in pBADmycHisB for over-expression and the r-SIF was purified using Ni-NTA affinity chromatography. Effect of r-SIF on mouse sperm motility, viability and on morphology was evaluated. Binding of r-SIF to mouse sperm was demonstrated by fluorescent labeling. Contraceptive efficacy of r-SIF was checked in murine model. Results Genomic library resulted in five hundred transformants; five clones were found positive for sperm immobilizing activity. The protein product of the insert DNA sequence in one of the transformants showed maximum sperm immobilizing activity. Sequence analysis of ORFs in the insert revealed homology to recX on both nucleotide and protein level. 40 μg of the purified r-SIF showed immediate spermicidal activity in vitro for mouse sperm. Scanning electron micrograph of the r-SIF treated sperm showed intense morphological damage to sperm. FITC labeled r-SIF showed highest fluorescence at the head region of the sperm. 5 μg of purified r-SIF exhibited a complete contraceptive effect in mouse model. Conclusion r-SIF could be seen as potential target to be developed as potent and safe vaginal contraceptive in future.